1998
DOI: 10.1037/0278-6133.17.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia and women's pursuit of personal goals: A daily process analysis.

Abstract: For 30 days, 50 women with primary fibromyalgia syndrome reported daily progress and effort toward a health-fitness and a social-interpersonal goal and the extent to which their pain and fatigue hindered their accomplishment. They also carried palmtop computers to assess their sleep and their pain, fatigue, and positive and negative mood throughout the day. Analyses of the person-day data set showed that on days during which pain or fatigue increased from morning to evening, participants perceived their goal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
99
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 42 publications
14
99
0
Order By: Relevance
“…The procedure was easily accepted and well tolerated by the subjects and produced reliable recordings: the 4 weeks of diary measurement accurately represented normal life in all subjects. The response rate of 88% is comparable to previous studies using electronic ESM-diaries Sorbi et al, 1996), although the use of a ®nan-cial reward for each completed diary yielded response rates as high as 99% (Af¯eck et al, , 1998. Nevertheless, in view of the relatively long period of sampling and the substantial number of questions per diary, compliance can be considered good.…”
Section: Discussionsupporting
confidence: 57%
“…The procedure was easily accepted and well tolerated by the subjects and produced reliable recordings: the 4 weeks of diary measurement accurately represented normal life in all subjects. The response rate of 88% is comparable to previous studies using electronic ESM-diaries Sorbi et al, 1996), although the use of a ®nan-cial reward for each completed diary yielded response rates as high as 99% (Af¯eck et al, , 1998. Nevertheless, in view of the relatively long period of sampling and the substantial number of questions per diary, compliance can be considered good.…”
Section: Discussionsupporting
confidence: 57%
“…Goal variables have been identified as a key determinant of both health promotion and health endangerment (Ewart, 1991;Karoly, 1991) and have been linked to conditions as diverse as heart disease, cancer, diabetes, alcohol and tobacco abuse, chronic pain, and hypochondriasis. For example, Affleck et al (1998) found that perceived progress toward personal goals attenuated the effect of pain on well-being in women with fibromyalgia. Women who reported more progress toward their goals on a given day experienced an increase in emotional well-being for that day that was independent of pain or fatigue levels.…”
Section: Personal Goals In the Lives Of Persons With Neuromuscular DImentioning
confidence: 99%
“…From a telephone survey in a sample from the general population, it was found that the presence of persistent or chronic pain strongly interfered with the construal of work goals, as reflected in lower levels of work goal value and self-efficacy, and higher levels of goal conflict between work-related and other goals 52 . Using a more finegrained daily process analysis in women with fibromyalgia, obtained from diary assessments, Affleck and colleagues 53 found that on days on which pain increased during the day, more goal hindrance was experienced.…”
Section: Goal Cognitionmentioning
confidence: 99%